Символічний вимір іміджу в сучасній політиці - Купцова, Ірина Ігорівна; Купцова, Ирина Игоревна; Kupcova, I. (My University, 2012)
In the article is reviewed the political image from the position of belonging to a symbolic system. The main approaches to understanding the role and functions of symbols in the political process are examined. The question of determining the place of image as a symbolic element is analyzed in the article. The author also examines the potential of symbols in the political reality.
Купцова І. І. Символічний вимір іміджу в сучасній політиці / І. І. Купцова // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України ; НУ ОЮА. – Одеса : Фенікс, 2012. – Вип.. 46. – С. 236-242.
Keywords: політичний імідж; символічні знакові системи; роль та функції символів у політичному процесі; ресурсний потенціал семіотичного простору у проектуванні політичної реальності; политический имидж; символические знаковые системы; роль и функции символов в политическом процессе; ресурсный потенциал семиотического пространства в проектировании политической реальности; political image; symbolic sign systems; the role and function of symbols in the political process; resource potential of the semiotic space in the design of political reality